College Culture and Student Satisfaction - Uprety, Raju; Chhetri, Sabina Baniya (Journal of Education and Research, 2014)
This study examines the relationship between college culture and student satisfaction.  It also examines the order of strength of relationship of college culture dimensions as perceived by students with student satisfaction. The study was conducted among 251 BBA students of various colleges located within Kathmandu and Lalitpur districts of Nepal using Denison Organizational Culture Survey Model. We measured student satisfaction using the questionnaire adopted from Hartman and Schmidt (1995) and Silva and Fernandes (2012). Our results indicated that college culture dimensions – involvement, adaptability, and consistency – related significantly to student satisfaction and the strength of relationship followed the order: involvement, adaptability and consistency.DOI: http://dx.doi.org/10.3126/jer.v4i1.10728ournal of Education and Research, March 2014, Vol. 4, No. 1, pp. 77-92